A critical evaluation of text difficulty development in ELT textbook series: A corpus-based approach using variability neighbor clustering. (June 2016) - Chen, Alvin Cheng-Hsien
Abstract: Although the importance of English Language Teaching (ELT) textbooks is widely acknowledged, previous evaluation of ELT materials has paid little attention to the appropriateness of the text difficulty development in a textbook series. The present study aims to assess the progression of text difficulty in different textbook series in Taiwan, the rationale of which is argued to be generalizable to other ELT contexts. Specifically, there are two methodological emphases. First, text difficulty has been quantitatively measured by the BNC corpus-based frequency lists and a comprehensive set of well-established readability formulas, considering both vocabulary and structure complexity of the texts; second, a clustering-based statistical algorithm—variability neighbor clustering—is utilized to identify the developmental stages in text difficulty on an empirical basis. This corpus-based computational method not only objectively determines the developmental gaps in a textbook series, but also identifies the direction of the difficulty progression in vocabulary and structure complexity. This rigorous textbook evaluation provides a common framework for the assessment of text difficulty progression in the ELT materials. Several pedagogical implications are drawn for EFL learners and teachers as well as ELT textbook developers.